A composite dust suppressant for suppressing dust in metal mines and preparation method thereof
By using composite dust inhibitors prepared with materials such as carboxymethylcellulose sodium, fatty alcohol polyoxyethylene ether and polyethylene glycol, the existing dust inhibitors have strong equipment corrosion, polluting the environment or high cost, and the effect of effectively inhibiting dust in metal mines and reducing environmental pollution and equipment corrosion risks is achieved.
Patent Information
- Application Number
- CN202410522994.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-04-28
AI Technical Summary
Existing dust inhibitors have problems such as strong corrosion in equipment, polluting the environment or being costly in inhibiting dust in metal mines, which are difficult to meet the needs of low prices, complex functions and reducing equipment corrosion and environmental pollution.
Sodium carboxymethylcellulose is used as the binder, fatty alcohol polyoxyethylene ether as the wetting agent and polyethylene glycol as the water retention agent, and a composite dust inhibitor is prepared by a simple physical mixing method to form a dust inhibitor with good bonding, wetting and water retention properties.
This dust inhibitor can effectively reduce dust diffusion, form a cured layer with strong wind corrosion resistance, reduce the risks of equipment corrosion and environmental pollution, and also has low preparation costs and good environmental protection performance.
Smart Images

Figure CN118530695B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dust control in environmental protection and mining processes, and in particular to a composite dust suppressant for suppressing dust in metal mines and a preparation method thereof. Background Art
[0002] The dust generated during mining is a potential threat to the environment and human health. In industrial production activities such as metal mining and metal processing, the generation of metal dust is also inevitable. Metal dust not only pollutes the working environment and increases equipment wear, but also poses a serious threat to the health of operators. Therefore, it is of great significance to control and reduce the spread of dust, and one of the effective ways to solve dust pollution is to avoid the generation of dust.
[0003] At present, the commonly used dust suppression methods in industry include physical covering and water spray, but these methods have their own shortcomings. For example, the physical covering method cannot completely suppress the spread of dust, the water spray method has poor dust suppression effect, and it is difficult to keep moisture for a long time. Through literature and practical research, it is found that chemical dust suppression is more efficient and has a longer dust suppression time than other dust suppression methods, but chemical dust suppressants have problems such as strong corrosion to equipment, environmental pollution or high cost due to their chemical composition. For example, sodium dodecyl sulfate containing sulfate ions is irritating to the human body and will cause environmental pollution when flowing into water bodies; and many scholars have shown that aqueous solutions of chlorides such as calcium chloride and magnesium chloride, which are commonly used as single-type dust suppressants, are acidic and highly corrosive, and have a certain risk of damage to soil and mechanical equipment, and have insufficient bonding properties for dust; some chemical materials such as cocamidopropyl betaine have good wetting properties, but the material cost is high and is not suitable for large-scale use in industry. Therefore, it is of great practical application value to develop a dust suppressant with low cost, complex functions and not easy to cause equipment corrosion. Summary of the invention
[0004] The purpose of the present invention is to prepare a composite dust suppressant for suppressing metal dust, which is not easy to corrode metal equipment and has better corrosion resistance than other dust suppressants, and can meet the needs of low price, composite functions and reducing equipment corrosion and environmental pollution.
[0005] The dust suppressant of the invention comprises a binder, a wetting agent and a water retaining agent, which are 100% by weight, and each component is composed of: 0.18-0.22% of the binder, 1-1.5% of the wetting agent, 2-2.5% of the water retaining agent, and the balance is water.
[0006] The binder is sodium carboxymethyl cellulose.
[0007] The wetting agent is fatty alcohol polyoxyethylene ether, and is in liquid form.
[0008] The water retaining agent is polyethylene glycol.
[0009] The preparation method of the above dust suppressant is as follows:
[0010] Under constant temperature water bath conditions, by weight percentage, the amount of binder is 0.18-0.22%, the amount of wetting agent is 1-1.5%, the amount of water retaining agent is 2-2.5%, and the balance is water. The binder and water retaining agent are added to the wetting agent solution in sequence, mixed and stirred to prepare a composite dust suppressant.
[0011] The temperature of the constant temperature water bath is 55-65°C.
[0012] The preparation method of the dust suppressant comprises the following steps:
[0013] 1) Add fatty alcohol polyoxyethylene ether into a beaker, add water and mix at a constant temperature of 55-65° C. and stir evenly to obtain a fatty alcohol polyoxyethylene ether solution;
[0014] 2) adding sodium carboxymethyl cellulose and polyethylene glycol to the solution obtained in step 1), and continuing stirring until the mixture is uniformly mixed to obtain the dust suppressant.
[0015] The prepared dust suppressant can be used for suppressing metal dust in mines.
[0016] Sodium carboxymethyl cellulose as a binder is a low-cost, non-toxic, non-corrosive and naturally degradable polymer material. It can increase the adhesion and adhesion of dust suppressants, making them better attached to the surface of metal dust, forming a protective film and reducing dust diffusion. It plays a role in fixing and stabilizing dust by improving the bonding strength of dust suppressants, effectively reducing the amount of small molecular dust floating in the air.
[0017] As a wetting agent (surfactant), fatty alcohol polyoxyethylene ether can reduce the surface tension of the solution, facilitate the combination between the solution and metal dust, increase surface activity, promote the mixing and dispersion of dust suppressant and dust, and form a uniform protective film.
[0018] As a water retaining agent, polyethylene glycol has good moisturizing properties and can absorb moisture in the air to form hydrates, so that the dust suppressant forms a moisturizing layer on the metal surface and reduces moisture loss. This can effectively extend the durability of the dust suppressant and improve the dust suppression effect.
[0019] The present invention prepares a dust suppressant by simply physically mixing three materials, namely, a binder, a water retainer and a wetting agent, by adding water, thereby improving the problem of poor performance of a single type of dust suppressant. The appropriate material ratio enables it to have good bonding performance while also having good fluidity, thereby enhancing the dust suppressant's ability to cover the dust surface and ensuring its applicability. The materials used for the dust suppressant are cheap and readily available, and are environmentally friendly, the preparation process is simple and convenient, and the preparation cost is low. In the process of performing dust suppression experiments on the dust suppressant, it is shown that after the dust suppressant is sprayed, a solidified layer with a certain strength can be formed on the dust surface, so that it has good wind erosion resistance, and has better moisture retention and pressure resistance, has good dust suppression performance, and effectively reduces the harmfulness of equipment corrosion, reduces the risk of environmental pollution, and is an economical, environmentally friendly, and efficient dust suppressant. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 a, b, c, and d are the water retention rates of the dust samples of the present invention at 25°C, 30°C, 35°C, and 40°C, respectively.
[0021] Figure 2 a and b are the loss rates of dust samples under wind speeds of 3 m / s and 20 m / s, respectively.
[0022] Figure 3 a and b are microscopic comparison diagrams of dust samples sprayed with dust suppressant and dust samples sprayed with tap water, respectively.
[0023] Figure 4 It is a comparison chart of uniform corrosion rate results of the present invention. DETAILED DESCRIPTION
[0024] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, the present invention is further described in detail below in conjunction with embodiments, but the present invention is not limited thereby.
[0025] The invention provides a composite dust suppressant for suppressing metal dust.
[0026] raw material
[0027] Sodium carboxymethyl cellulose: Sodium carboxymethyl cellulose produced by Beijing Mairida Technology Co., Ltd. is selected and is in the form of white powder.
[0028] Fatty alcohol polyoxyethylene ether: Fatty alcohol polyoxyethylene ether from Shandong Yousuo Chemical Technology Co., Ltd. is a white viscous liquid.
[0029] Polyethylene glycol: Polyethylene glycol produced by Shanghai McLean Biochemical Technology Co., Ltd. is used, which is in the form of white crystals.
[0030] It should be noted that the sources of the above reagents cannot be used as a limitation to the present invention, and reagents from other manufacturers with quality not lower than that of similar products can also be used.
[0031] Embodiment 1:
[0032] The dust suppressant is calculated by weight percentage to be 100%, wherein the amount of sodium carboxymethyl cellulose is 0.2%, the amount of fatty alcohol polyoxyethylene ether is 1.0%, the amount of polyethylene glycol is 2.17%, and the balance is water.
[0033] Preparation steps:
[0034] 1) Add fatty alcohol polyoxyethylene ether into a beaker, add water and mix at a constant temperature of 60° C. and stir to obtain a fatty alcohol polyoxyethylene ether solution;
[0035] 2) adding sodium carboxymethyl cellulose and polyethylene glycol to the solution obtained in step 1), and continuing stirring until the mixture is uniformly mixed to obtain a dust suppressant.
[0036] Secondly, the dust suppressant was subjected to the following series of characterization experiments:
[0037] 1. Anti-evaporation test
[0038] First weigh 10g of dust into a watch glass, then add the prepared dust suppressant solution at 2L / m 2 The treated dust samples were placed in drying ovens at 25℃, 30℃, 35℃ and 40℃ respectively for 8 hours of continuous evaporation. The dust samples were weighed every hour to observe the changes in moisture content of dust samples at different temperatures over time.
[0039] Calculate the moisture content of dust according to formula (1):
[0040]
[0041] Where:
[0042] P—water retention rate (%);
[0043] m 0 —The weight of the culture dish before spraying the water retaining agent solution, g;
[0044] m—weight of the culture dish after spraying the water retaining agent solution, g;
[0045] m x —Weight of the culture dish after drying for a period of time, g.
[0046] The experimental results are as follows Figure 1As shown. It can be seen from the figure that the dust sample under the dust suppressant has a significant anti-evaporation effect compared with tap water. Under the temperature conditions of 25℃ and 30℃, during the first 3 hours, the water retention rate of the dust samples containing water and dust suppressants was basically the same, and the water retention rate of the dust samples containing dust suppressants was more than 10% higher than that of the dust samples containing water. After 7 hours, the water retention rate of the dust samples remained basically unchanged, and the water retention rate of the dust samples containing dust suppressants was about twice that of the dust samples containing water. With the increase of temperature, the water retention rate of the dust samples showed a downward trend, but the moisture content of the dust samples under tap water decreased faster. At the temperature of 35℃ and 40℃, the dust samples containing dust suppressants showed a more obvious downward trend at first, but after 3 hours, the rate of decrease of the water retention rate of the dust samples containing dust suppressants was much slower, showing its good water retention effect. From the above results, it can be seen that the dust samples containing dust suppressants can retain a higher moisture content than the dust samples containing water at different temperatures, indicating that the dust treated with dust suppressants has better water retention performance.
[0047] 2. Anti-wind erosion test
[0048] This experiment simulates different wind speeds in reality through different fans to verify the anti-wind erosion effect of dust at different wind speeds after spraying dust suppressants. Use culture dishes of equal size, pile equal amounts of dust on the surface of the culture dishes to form a small mound, spray an appropriate amount of water or dust suppressant on the dust surface according to the surface area of the mound, then place the dust sample sprayed with dust suppressant and tap water in a natural environment for 6 hours and weigh it, finally place the dust sample in an environment with different wind speeds, blow it at different wind speeds for 4 hours, weigh it every 1 hour, and calculate the final loss rate. The larger the loss rate, the weaker its wind erosion resistance. Use formula (2) to calculate the mound loss rate:
[0049]
[0050] Where:
[0051] E—loss rate, %;
[0052] W 1 —Mass of dust sample before blowing, g;
[0053] W 2 —Mass of dust sample after erosion, g.
[0054] Figure 2The loss rate of dust samples sprayed with water and dust suppressant under the conditions of wind speed of 3.5m / s (a) and 20m / s (b) changes with time. As can be seen from the figure, the loss rate of dust samples sprayed with dust suppressant is only 0.025% at low wind speed, while the loss rate of dust samples sprayed with tap water is 0.1% at this wind speed; with the increase of wind speed, the dust loss rate of dust samples sprayed with dust suppressant increases slowly, while the dust loss rate of dust samples sprayed with tap water increases significantly; when the wind speed increases to 20m / s, the loss rate of dust samples containing water reaches 24.7%, while the loss rate of dust samples sprayed with dust suppressant also increases to 0.9% at this time. This is because the wind speed is too high, causing some small particles in the dust samples to separate from the dust body and be blown away by the wind, so the loss rate increases. However, compared with the dust samples sprayed with tap water, the loss rate of dust samples sprayed with dust suppressant is much smaller than the loss rate of dust samples sprayed with tap water. Therefore, the dust suppressant exhibits very good anti-wind erosion performance.
[0055] 3. Scanning electron microscopy (SEM) experiment
[0056] The dust sample after spraying the dust suppressant solution and tap water was evenly ground into solid powder particles with a particle size of less than 100um. The conductive glue was tightly pasted on the metal strip, and then about 0.1mg of sample powder was scooped with a medicine spoon and evenly spread on the conductive glue. The floating powder on the surface of the experimental sample was blown off with an air gun and then placed in a sealed bag for packaging. Then, the MCIOOO gold spraying instrument produced by HITACHI was used to spray gold on it. After the gold spraying treatment, the microscopic morphology was photographed using a Czech TESCAN MIRA LMS scanning electron microscope.
[0057] The scan results are as follows Figure 3 As shown in the figure, under the same magnification, it can be seen that there are more fine and small particles on the surface of the dust sample sprayed with tap water, the dust particles are small in size, and are relatively loosely distributed within the visible range, and the space between adjacent particles is large, and the surface is relatively smooth. A small part of the dust particles form blocks, which is because there is still a small amount of water inside the dust, and agglomerates are formed after drying. In the dust sample sprayed with dust suppressants, the pores between the dust particles are significantly reduced, and many branch-like fine particles are attached to the surface of larger dust particles, and it can be clearly seen that some small dust particles gather together to form larger particles. It can be seen that the composite dust suppressant can adhere to the surface of dust particles, so that the fine particles on the dust surface are bonded into blocks, and it has a good consolidation effect. By forming a tight structure on the surface, the porosity of the dust is reduced, thereby forming a better wind erosion resistance.
[0058] 4. Anti-corrosion test
[0059] During the spraying process of dust suppressants, composite dust suppressants may come into contact with metal objects such as spraying vehicles, equipment, loading and unloading tools, etc. Therefore, it is necessary to conduct corrosion tests on dust suppressants to examine their anti-corrosion performance. This study selected important components (ordinary carbon steel, ferritic stainless steel and aluminum alloy) that may come into contact with composite dust suppressants. Two types of dust suppressants, a 1:100 type white crust dust suppressant marked as "corrosion-free" (No. 1 dust suppressant) and a dust suppressant marked as "environmentally friendly" (No. 2 dust suppressant), and a group of tap water were selected as the control group. The uniform corrosion performance test was carried out according to the "Metal Materials Laboratory Uniform Corrosion Full Immersion Test Method" (GB / T7901-1999, 1999). The sample size was 50 mm (length) × 25 mm (width) × 2 mm (height), and the test time was 96 h. The corrosion rate was calculated using formula (3).
[0060]
[0061] Where:
[0062] R—corrosion rate, mm / a;
[0063] M—sample mass before test, g;
[0064] M 1 —Mass of sample after test, g;
[0065] S—total sample area, mm 2 ;
[0066] T—test time, h;
[0067] D—Material density, kg / m 2 .
[0068] The uniform corrosion results of the composite dust suppressant and the other three control groups are shown in Table 1. For stainless steel, the uniform corrosion rate of the composite dust suppressant is the same as that of tap water, which is 0.0009mm / a. The corrosion rates of the other two dust suppressants on stainless steel are 0.0018mm / a and 0.0046mm / a respectively; for aluminum alloy, the uniform corrosion rate of the dust suppressant is 0.0080mm / a, slightly higher than the 0.0054mm / a of tap water, but much lower than the corrosion rates of the other two dust suppressants, which are 0.016 and 0.0428. The corrosion rates of the other two dust suppressants on aluminum alloy are 2 times and 5.35 times that of the composite dust suppressant respectively; for ordinary carbon steel, the corrosion rates of the four solutions have increased, with water being the lowest, followed by the composite dust suppressant, and the corrosion rates of the other two dust suppressants on steel being 133% and 204% of the composite dust suppressant respectively. The above results show that the dust suppressant prepared by the present invention has better anti-corrosion performance than other dust suppressants, and can effectively reduce the corrosion of metal equipment and environmental pollution during metal mining. In addition, the corrosion rates of the dust suppressant prepared by the present invention are within the requirements of relevant technical standards (TB / T3210.1-2009 stipulates that the corrosion rate requirements for steel and aluminum alloy are less than or equal to 5×10 -5 m / a、3×10 -5 m / a), and the corrosion rate of dust suppressant on carbon steel and aluminum alloy was calculated to be 4.74×10 -5 m / a, 0.8×10 -5 m / a. Therefore, the dust suppressant can be used for dust suppression on mine roads and mining working faces.
[0069] Table 1 Corrosive uniformity test results
[0070]
[0071] The physical and chemical properties of dust suppressants with different ratios are tested below, and the results are compared.
[0072] Test Method
[0073] The viscosity, surface tension and pH value of dust suppressants were determined using the following methods:
[0074] Viscosity test
[0075] The viscosity of the dust suppressant solution was measured at 25°C using a digital viscometer (NDJ-5S) according to GB / T10247-2007 "Viscosity Measurement Method". Use a No. 0 rotor and set the speed to 6 to 60 rpm. Measure each sample three times and calculate the average value.
[0076] Surface tension test
[0077] Place the prepared dust suppressant solution sample on the sample table and measure the surface tension of the solution with a BZY-201 surface tension tester in accordance with the standard GB / T22237-2008 "Surface Tension Measurement Method". Test each concentration 3 times and calculate the average value. Use deionized water as the control group.
[0078] pH Test
[0079] Prepare dust suppressant solution and use pH-902 pH test pen to measure the pH value of the solution according to GB / T 14518-93. First calibrate the instrument, clean the measuring electrode with distilled water, and put it into standard buffer solution of pH=6.8 and pH=9.18 for calibration. After calibration, measure the pH value of the dust suppressant solution. First, stir the solution evenly with a glass rod, then insert the clean electrode into the test solution and read the pH value on the display.
[0080] Embodiment 2:
[0081] The dust suppressant has a total of 100 g, which contains 0.2 g of sodium carboxymethyl cellulose, 1 g of fatty alcohol polyoxyethylene ether, 2 g of polyethylene glycol, and the balance is water. Fatty alcohol polyoxyethylene ether and water are first added and stirred until dissolved, and then sodium carboxymethyl cellulose and polyethylene glycol are added, and the mixture is placed in a magnetic stirring water bath and stirred until uniformly mixed to obtain the dust suppressant.
[0082] Embodiment 3:
[0083] The dust suppressant has a total of 100 g, which contains 0.18 g of sodium carboxymethyl cellulose, 1 g of fatty alcohol polyoxyethylene ether, 2.5 g of polyethylene glycol, and the balance is water. Fatty alcohol polyoxyethylene ether and water are first added and stirred until dissolved, and then sodium carboxymethyl cellulose and polyethylene glycol are added, and the mixture is placed in a magnetic stirring water bath and stirred until uniformly mixed to obtain the dust suppressant.
[0084] The dust suppressants obtained in Examples 1-3 were tested, and the results of viscosity, surface tension and pH value were shown in Table 2.
[0085] Table 2 Physical and chemical test results of dust suppressants
[0086]
[0087] In summary, through anti-evaporation, anti-wind erosion, anti-corrosion experiments and scanning electron microscope tests, it is proved that the composite dust suppressant provided by the present invention has good water retention performance under the temperature conditions of 25°C-40°C, and has good anti-wind erosion performance under low wind speed and high wind speed. Compared with the traditional water spray dust suppression method, it has obvious advantages, and its corrosion to steel is much lower than the two commercially available dust suppressants, and has lower corrosion. By comparison, it can be seen that under the ratio within the range of the present invention, the physical and chemical properties of the dust suppressant are better, meeting the viscosity and fluidity requirements mentioned above, and having lower surface tension, the effect of wetting dust is more significant, and the pH value of the dust suppressant is also within the requirements of the relevant standards. Therefore, the dust suppressant has good use value and application prospects.
[0088] It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a composite dust suppressant for suppressing dust in metal mines, characterized in that: The composite dust suppressant includes a binder, a wetting agent, and a water retaining agent, which together account for 100% by weight. The components are composed of 0.18-0.22% of the binder, 1-1.5% of the wetting agent, 2-2.5% of the water retaining agent, and the balance is water. The binder and the water retaining agent are sequentially added to the wetting agent solution through a constant temperature water bath of 55-65°C, and the mixture is mixed and stirred. The binder is sodium carboxymethyl cellulose, the wetting agent is fatty alcohol polyoxyethylene ether, and the water retaining agent is polyethylene glycol.
2. The method for preparing a composite dust suppressant for suppressing dust in metal mines according to claim 1, characterized in that: The specific steps are as follows: 1) Add fatty alcohol polyoxyethylene ether into a beaker, add water and mix at a constant temperature of 55-65° C. and stir evenly to obtain a fatty alcohol polyoxyethylene ether solution; 2) Adding sodium carboxymethyl cellulose and polyethylene glycol to the solution obtained in step 1), and continuing to stir until the mixture is uniformly mixed to obtain the composite dust suppressant.
3. The composite dust suppressant prepared according to any one of claims 1 to 2 is used for suppressing metal dust in mines.
Citation Information
Patent Citations
Development of natural environment-friendly open-pit coal pile covering agent
CN109852347A